Consumer hopefulness: construct, relevance to internet marketing, antecedents and consequences. (12th May 2004) - MacInnis, Deborah J.; de Mello, Gustavo; Patrick, Vanessa M.
This paper examines the concept of consumer hopefulness as an important driver of consumption. Hopefulness is defined as a positive feeling evoked in response to an outcome appraised as goal congruent and possible. This positively valenced emotion arises in everyday consumption as consumers evaluate their current state and try to determine ways in which consumption can make for a better, happier future self. The paper differentiates the construct of hopefulness from related constructs such as self-efficacy, expectations, and optimism. It also focuses on the consumption domains in which hopefulness arises. Most relevant to advertising and the internet, the paper identifies factors that affect hopefulness, as well as tactics that influence these factors (and hence the level of hopefulness that consumers experience). The marketing relevant outcomes of consumer hopefulness are also articulated, and directions for future research are specified.